Makna Al Quran Diturunkan Sebagai Rahmat Dalam Tafsir Asy-Sya’rawi - Mush'ab; Akhmad sulthoni; Fajar Novitasari (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The Qur'an, as the Holy Book of Muslims, serves as a guide as well as Mercy for all nature (rahmatan lil-‘alamīn). This study aims to examine the meaning of the revelation of the Qur'an as a mercy according to the perspective of tafsir Sheikh Muhammad Mutawalli Ash-Sha'rawi,because there are many people who do not know the meaning of the Qur'an was revealed as a mercy. This study uses a qualitative approach through literature studies with thematic interpretation method (maudhū'ī). The primary source is taken from the work of Khawa'ir Ash-Sha'rāwī Ḥaul al-Qura'ān al-Karīm, and includes secondary references from the supporting literature. The results showed that Ash-Sha'rawi interpreted the Qur'an as a mercy that includes spiritual, moral, social, and intellectual dimensions. The Qur'an is not only a cure for diseases of the heart and soul, but also serves as a comprehensive guide to life and a solution to the challenges of the Times. This is a blessing only for those who have faith. Interpretation of verses such as Q.S. al-A'rāf: 52 and 203, Yūnus: 57, an-Naīl: 89, al-Isrā’: 82, and Luqmān: 3 reinforce that the Qur'an is a clear manifestation of Allah's compassion, which guides man towards the salvation of this world and the hereafter. Thus, the Qur'an as a mercy is not just a theoretical concept, but a real applicable principle of life, which, if properly understood and practiced, is able to contribute to the happiness and well-being of mankind.